Answer:
These two numbers are <em>-1 and -6 </em>respectively.
Step-by-step explanation:
Suppose first number is x and the second number is y.
Then according to question-
( x + y ) = -7 ..............................(i)
x × y = 6 ................................(ii)
As we know that-
<em>
=
.......................(iii)</em>
Now, Putting values of equation (i), (ii) in equation (iii)-
We get,
=
- 4 × 6
= 49 - 24
= 25
( x - y ) = ![\sqrt{25}](https://tex.z-dn.net/?f=%5Csqrt%7B25%7D)
( x - y ) = 5<em>..........................(iv)</em>
After adding equation (i) and (iv)-
( x + y ) = -7
<u>( x - y ) = 5</u>
<u> 2 x = -2</u>
x = -2 /2
<em>x = -1 </em>
Now put x = -1 in equation (i)-
We get,
y = -7 - x
y = -7 - (- 1)
y = - 7 + 1
y = -6
<em>Hence the both numbers x and y are -1, -6 respectively.</em>